Applying spatial decision support for maternal mortality analysis in a Brazilian state - Thiago Poleto; Victor Diogho Heuer de Carvalho; Rodrigo Cleiton Paiva de Oliveira (Socioeconomic Analytics)
The interface between Decision Support Systems (DSS) and Geographical Information Sys-tems (GIS) generates Spatial Decision Support Systems (SDSS) which aid in the deci-sion-making process, particularly in situations where spatial attributes play a pivotal role in achieving accurate conclusions. By integrating conventional decision criteria with spatial crite-ria and visualization through the adoption of SDSS and geographic information systems tech-nologies, a comprehensive analysis is ensured. The primary aim of this research is to exemplify an application of SDSS to support analyses and decisions on a specific issue in Public Health. The focus lies on assessing cities within the state of Pernambuco (Brazil) that exhibit the high-est rates of maternal mortality. This approach promises to offer valuable insights and aid in making informed decisions to address critical maternal health issues in the region.